Analisis Komparatif Persepsi Kualitas Pelayanan Provider Telkomsel dan Indosat (Studi pada Pengguna Layanan Provider Telkomsel dan Indosat di Surabaya) - Zakiyah Febrianti; Lisa Sulistyawati (Universitas Batanghari, 2022)
The telecommunications sector is the most important as a supporter of the economic growth of a city, especially the city of Surabaya. And a city that has a very rapid growth, is a potential market for the telecommunications industry. Both have become a law of reciprocity market. This study aims to identify and analyze differences in perceptions of service quality between Telkomsel providers and Indosat providers. The population used in this study were users of Telkomsel and Indosat service providers in the Surabaya area. The sample required is 50 respondents, namely 50 users who are currently or have used the Telkomsel and Indosat provider services. The sampling method used in this research is quota sampling. The type of data used in this study is primary data, namely data collected or obtained directly from the research object. The data collection technique used in this study was a questionnaire. The data analysis technique used in this research is comparative analysis. Thus, the results of this study are that there is a significant difference in the results of the assessment of service quality perceptions of Telkomsel Providers and Indosat Providers.